2016
DOI: 10.11152/mu.2013.2066.183.hgh
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency sonography in the evaluation of nail psoriasis.

Abstract: Aim: To evaluate the morphostructural aspects and nail vascularity in the nail unit of patients with psoriasis, and to evaluate whether there are differences among psoriatic patients with and without nail involvement. Material and methods: Nail plates and nail bed changes, nailfold vessel resistance index (NVRI), power and color Doppler blood flow appearances were investigated in 23 patients with moderate-to-severe psoriasis, with and without nail involvement, and compared to those of 11 healthy participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 20 publications
5
43
2
1
Order By: Relevance
“…In our study, patients with psoriasis had a higher NPT in comparison with HCs (p<0.001). Gisondi et al and Marina et al found similar results in their studies [36,39]. Patients with PND had a significantly higher NVRI than HCs in the present study (p<0.001).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In our study, patients with psoriasis had a higher NPT in comparison with HCs (p<0.001). Gisondi et al and Marina et al found similar results in their studies [36,39]. Patients with PND had a significantly higher NVRI than HCs in the present study (p<0.001).…”
Section: Discussionsupporting
confidence: 80%
“…Patients with PND had a significantly higher NVRI than HCs in the present study (p<0.001). Similar NVRI results were reported by El-Ahmed et al and Marina et al [30,36]. These results can be explained by the decreased blood supply in the nail bed in psoriatic patients due to endothelial dysfunction and wall vessel thickening [36].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Study subjects were appropriately described in all included studies, and valid methods to determine the presence of the pathological condition were used and extensively described. The statistical analysis plan was deemed appropriate for the 15 studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Overall, the risk of bias was assessed as moderate to high due to the small sample size of the studies.…”
Section: Assessment Of Biasmentioning
confidence: 99%